2023
DOI: 10.3390/foods12081681
|View full text |Cite
|
Sign up to set email alerts
|

FEDformer-Based Paddy Quality Assessment Model Affected by Toxin Change in Different Storage Environments

Abstract: The storage environment can significantly impact paddy quality, which is vital to human health. Changes in storage can cause growth of fungi that affects grain quality. This study analyzed grain storage monitoring data from over 20 regions and found that five factors are essential in predicting quality changes during storage. The study combined these factors with the FEDformer (Frequency Enhanced Decomposed Transformer for Long-term Series Forecasting) model and k-medoids algorithm to construct a paddy quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…Previous studies have demonstrated that lower temperatures can effectively inhibit microbial growth and toxin production [44,45]. Additionally, higher temperatures and moisture levels are associated with increased accumulation of aflatoxin B1 and ochratoxin A, with aflatoxin B1 reaching its highest concentration [46]. However, the rice grains stored with the condition of quasi-low temperature had a higher content of ochratoxin A and aflatoxin B1.…”
Section: Comparison Of Mycotoxins Of Rice Grains Stored Under Differe...mentioning
confidence: 95%
“…Previous studies have demonstrated that lower temperatures can effectively inhibit microbial growth and toxin production [44,45]. Additionally, higher temperatures and moisture levels are associated with increased accumulation of aflatoxin B1 and ochratoxin A, with aflatoxin B1 reaching its highest concentration [46]. However, the rice grains stored with the condition of quasi-low temperature had a higher content of ochratoxin A and aflatoxin B1.…”
Section: Comparison Of Mycotoxins Of Rice Grains Stored Under Differe...mentioning
confidence: 95%
“…Rice is a dietary staple for over half of the world's population [1], with harvested rice often being processed into either white rice or brown rice for consumption. The two main types of rice processing are as follows: firstly, processing rice by removing the hull from the paddy and producing brown rice, and secondly, processing brown rice by removing the bran and then polishing it to obtain white rice [2].…”
Section: Introductionmentioning
confidence: 99%